Hubungan Antara Kepimpinan Transformasional Dengan Komitmen Organisasi : Kajian Empirikal di Politeknik Sultan Abdul Halim Mu'Adzam Shah - Zulmajdi, Alias (2002)

(untitled)
The purpose of this study was to examine the relationship between transformational leadership behaviour of the head of departments and organizational commitment of the lecturers of Politeknik Sultan Abdul Halim Mu'adzam Shah. Two hundreds lecturers from 6 departments were selected as respondents. This study has used the questionnaires as the survey instrument upon which the response rate was 85%. The data collected was analyzed following the descriptive and differential research guidelines through SPSS program. The finding showed that there was no significant relationship between personal characteristics and organizational commitment of POLIMAS's lecturers. The lecturers' level of organizational commitment was found to be moderate. It also showed that the lecturers have the perception that their head of departments show a moderate level of transformational leadership behaviour. The findings also showed that there was a significant relationship between overall transformational leadership behaviour of the heads of departments and organizational commitment of the lecturers.